Distributional effects of early childhood programs and business incentives and their implications for policy - Timothy J. Bartik (W.E. Upjohn Institute for Employment Research, 2009)
This paper is a draft of Chapter 8 of a planned book, Preschool and Jobs: Human Development as Economic Development, and Vice Versa. This book analyzes early childhood programs' effects on regional economic development. Four early childhood programs are considered: 1) universally accessible preschool for four-year-olds of similar quality to the Chicago Child Parent Center program; 2) the Abecedarian program, which provides disadvantaged children with high-quality child care and preschool from infancy to age five; 3) the Nurse Family Partnership, which provides low-income first-time mothers with nurse home visitors from the prenatal period until the child is age two; and 4) the Parent Child-Home program, which provides home visits and educational toys and books to disadvantaged families when the child is between the ages of 2 and 3. The book considers the main benefit of state economic development to be the resulting increase in earnings of the original residents who stay in that state. Early childhood programs increase residents' earnings largely by increasing the quantity and quality of local labor supply. These programs will increase the employability and wages of former child participants in these programs. The book compares the effects on local earnings of early childhood programs with the effects of business incentives (e.g., property tax abatements). Business incentives increase local residents' earnings by increasing the quantity and/or quality of local labor demand. This chapter considers the effects of early childhood programs and business incentives on the income distribution. A key issue is whether early childhood programs should be targeted on the poor, or made universally available for free. Relevant considerations in addressing this issue include how benefits of early childhood programs benefit with family income, and the political feasibility of targeted versus universal programs.
Keywords: J13; J24; I21; R23; R31; R30; 330